The Moderating Role of Electronic Word of Mouth (eWOM) in the Influence of Perceived Value on Repurchase Intention - Aldrich Alfatera Unpapar (PT FORMOSA CENDEKIA GLOBAL, 2021)
The purpose of this research is to determine whether word of mouth which has developed into electronic (eWOM) in the digitalization era can strengthen or weaken the influence of the perceived value received by customers from previous purchases to repurchase or not. This study uses a quantitative approach, whereas the method of data collection was purposive sampling and has determined as many as 116 samples. The population in this research are followers of Shopee Indonesia in Instagram, with the various characteristics that have been determined by researchers to be taken as a sample for this research. The method of data analysis using equations from Cohen et al. (1975) in the journal of Sharma et al. (1981). The regression analysis is based on the researcher's comprehension of the negligibility correlation between moderation and predictor variables. Based on the results, Perceived Value has a significant and positive effect on Repurchase Intention, and the regression model analysis was found that the inclusion of the moderation variable, strengthened the influence of Perceived Value on Repurchase Intention by 61,5% from the previous results (55,8%).